Postural Balance in Women with Osteoporosis and Effective Factors - Duygu Ünlüsoy; Ece Aydoğ; İhsan Ünlüsoy (Galenos Yayinevi, 2011)
Introduction: The most common cause of mortality and morbidity among osteoporotic individuals is bone fracture which in many cases is a direct result of falls. Individual factors contributing to the risk of fall are poor postural balance and lack of muscle strength. Our aims were to assess postural dynamic balance in osteoporotic women and to describe the effective factors on the balance performance. Methods: Twenty osteoporotic women with kyphosis, 50 osteoporotic women without kyphosis, and 30 healthy women were included in the study. Anterior/Posterior (AP), Medial/Lateral (ML) and Overall (OA) stability indices were obtained using Biodex Stability System (Biodex Medical System, Shirley, NY). Subjects were tested both with eyes open and eyes closed. Quadriceps-hamstring muscles' strength were measured with isokinetic system at angular speeds of 60-180-300°/sec. Results: OA, AP, ML stability indices in the group with osteoporosis were found to be statistically significantly higher in the open-eyed balance test. When a correlation analysis was performed on all osteoporotic patients, a negative correlation was detected between balance stability indices and knee flexion-extension strength at 60°/sec and knee flexion strength at 300°/sec. Multivariable regression analysis revealed knee extension strength at 60°/sec to be the most effective factor contributing to balance in osteoporotic patients. Conclusion: Postural balance in osteoporotic women presenting is significantly worse than in the healthy women and the factor exerting the greatest influence on balance is quadriceps muscle strength. Therefore, particular importance must be given to balance and quadriceps strengthening exercises in order to prevent falls in osteoporotic patients. (Turkish Journal of Osteoporosis 2011;17:37-43)